Endogenous formation of 1-propanol and methanol after consumption of alcoholic beverages. (August 2021) - Wunder, Cora; Weber, Corinna; Paulke, Alexander; Koelzer, Sarah C.; Holz, Franziska; Toennes, Stefan W.
Highlights: Investigation of endogenous formation of 1-propanol and methanol after consumption of an alcoholic beverage. In a drinking experiment 24 volunteers consumed congener free vodka. The kinetic parameters of ethanol, methanol and 1-propanol were evaluated. Results confirm the formation of 1-propanol and methanol. Evaluation of concentrations of 1-propanol must include the endogenous formation. Abstract: Introduction: In cases of drunk-driving, allegations that alcohol has been consumed after the incident, are proved by analyzing congener alcohols in the blood sample. 1-Propanol, one of the main congener compounds, was tested, whether it is also endogenously formed when a person has consumed alcoholic beverages. Methods: Eleven male and 13 female volunteers consumed congener-free vodka (37.5 vol% ethanol, individual doses: 0.15–0.32 l) within one hour. Blood samples were taken up to 10 h and analyzed for ethanol and congener alcohols by headspace gas chromatography-mass spectrometry. Results: Ethanol concentrations reached in blood a maximum of 0.65–1.23 g/l and decreased by 0.18 g/l/h (median values). Of the congener alcohols analyzed, only methanol and 1-propanol were detected in the plasma samples of all subjects. The endogenous methanol concentration increased from 0.66 mg/l by 0.22 mg/l/h to 2.19 mg/l (medians). 1-Propanol was not detected prior to alcohol consumption. Maximum concentrations of 0.10–0.32 mg/L were measured after 1.0–4.5 h. A plateau of the 1-propanol concentration was observed in the plasma samples of the 18 subjects lasting for 0.5–4.0 h and this alcohol was completely eliminated at ethanol concentrations of 0.17 g/l (median, range 0.03–0.55 g/l). Conclusion: The results of the study confirm the formation of 1-propanol after consumption of 1-propanol-free beverages, which should be taken into account when evaluating its concentration.